Tolerance to Light of Patients Suffering From Infectious Keratitis. Issue 1 (January 2021) - Courrier, Emilie; Lambert, Victor; Renault, Didier; Garcin, Thibaud; Moine, Baptiste; Herbepin, Pascal; Thuret, Gilles; Gain, Philippe
Abstract : Purpose: With very photophobic patients, the advantages of red or near infrared light to develop new ophthalmology imaging devices seem obvious: no or little glare, possibility of long signal integration, no phototoxicity, and lesser autofluorescence of ocular tissues. Nevertheless, in this range, the shortest possible wavelength facilitates signal detection. The aim of this study was, thus, to determine the maximal irradiance tolerated with 6 wavelengths: 2 red, 2 far red, and 1 near infrared lights to determine the shortest wavelength well tolerated by patients, in comparison with the standard cobalt blue light of ophthalmology slitlamp. Methods: An interventional, monocentric, single-group assignment study was conducted on 30 eyes of 30 patients with infectious keratitis. Thanks to a customized machine, the photophobic eye was exposed to the 6 lights with increasing intensity. The patients switched off the light when the discomfort was too elevated. The maximal cumulative irradiance possible at 482, 650, 675, 700, 750, and 800 nm were 171, 689, 759, 862, 920, and 889 mW/cm 2, respectively. Results: The maximal cumulative irradiance tolerated by patients increased significantly with wavelength ( P < 0.001), but the difference was not significant between each increment: red at 675 nm gave a significantly higher cumulative irradiance than blue at 482 nm; red at 700 nm did not provide significant gain compared with 675 nm; and far red at 750 nm still provided additional gain compared with 700 nm, but no significant gain was observed between 750 and 800 nm. The shortest wavelengths were stopped more quickly, and more than 50% of patients reached the maximum irradiance delivered by the source at 750 and 800 nm. Conclusions: We demonstrate that a light source at 750 and 800 nm can be used for ophthalmic imaging with good tolerance in photophobic patients. Clinical trial registration: NCT03586505. Abstract : Supplemental Digital Content is Available in the Text.